2009
DOI: 10.1063/1.3171615
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of nonlinear optical properties due to large amplitude anharmonic vibrational motions: Umbrella motion in NH3

Abstract: A general reduced dimensionality finite field nuclear relaxation method for calculating vibrational nonlinear optical properties of molecules with large contributions due to anharmonic motions is introduced. In an initial application to the umbrella ͑inversion͒ motion of NH 3 it is found that difficulties associated with a conventional single well treatment are overcome and that the particular definition of the inversion coordinate is not important. Future applications are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 60 publications
(87 reference statements)
0
30
0
1
Order By: Relevance
“…Electron correlation effects were taken into account at the CCSD level through the coupled cluster linear, quadratic, and cubic response theories [38][39][40] implemented in the DALTON program. 41 In spite of the high level of the electron correlation treatment, the quality of the function basis set, and the careful computation of the vibrational corrections, a drawback of the methodology is that the normal coordinate approximation may not be an adequate model for large-amplitude modes, 13,14,16 as the modes related to the hydroxyl group. The discrepancy between the calculated vibrational frequency of the OH torsion mode ͑mode 1͒ and the experimental result, for instance, is an indication that the normal coordinate approximation is not reliable for this mode.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electron correlation effects were taken into account at the CCSD level through the coupled cluster linear, quadratic, and cubic response theories [38][39][40] implemented in the DALTON program. 41 In spite of the high level of the electron correlation treatment, the quality of the function basis set, and the careful computation of the vibrational corrections, a drawback of the methodology is that the normal coordinate approximation may not be an adequate model for large-amplitude modes, 13,14,16 as the modes related to the hydroxyl group. The discrepancy between the calculated vibrational frequency of the OH torsion mode ͑mode 1͒ and the experimental result, for instance, is an indication that the normal coordinate approximation is not reliable for this mode.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 It has been shown that in many circumstances the corrections arising from the molecular vibrations are of similar magnitude, or even larger, than the electronic counterparts. [7][8][9][10][11][12][13][14][15][16] For systems on condensed phase the influence of the medium must also be considered, being the description of solvated systems usually made through simulation methods ͑molecular dynamics or Monte Carlo͒ or continuum models. [17][18][19][20][21][22][23] Methanol has been the subject of a number of recent theoretical and experimental investigations.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of the nuclear motion contributions to various electromagnetic molecular properties is by now well understood. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] The zero-point vibrational corrections (ZPVCs) are proved to be non-negligible for the electron paramagnetic resonance (EPR), 18,20 nuclear magnetic resonance (NMR), 8,15,21 and non-linear optical (NLO) properties. 9,22 The so-called pure vibrational contributions to NLO properties 23 are often comparable or even larger in magnitude than that due to electronic motions.…”
Section: Introductionmentioning
confidence: 99%
“…9,22 The so-called pure vibrational contributions to NLO properties 23 are often comparable or even larger in magnitude than that due to electronic motions. 3,4,[9][10][11] Moreover, some of the experimentally observed effects, such as temperature dependence and isotope shifts of electric and magnetic properties, are entirely due to the effect of molecular vibrations and rotations. 15 Several successful methods for evaluating the rovibrational contributions to various molecular properties were formulated using the perturbation theory (PT) approach over the last few decades.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a more rigorous study of the higher‐order vibrational properties would require the use of methods as employed for the NH 3 molecule in Ref. and will be the subject of a forthcoming study.…”
Section: Discussionmentioning
confidence: 99%